2015
DOI: 10.1111/idj.12160
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of evidence-based dentistry into practice: analysis of awareness, perceptions and attitudes of dentists in the World Dental Federation–European Regional Organization zone

Abstract: Based on evidence-based dentistry (EBD) being a relatively new concept in dentistry, the attitudes, perceptions and level of awareness of dentists regarding EBD, and perceived barriers to its implementation into daily practice, were comparatively analysed in six countries of the FDI (World Dental Federation-Federation Dentaire Internationale)-European Regional Organization (ERO) zone (France, Georgia, Poland, Portugal, Slovakia and Turkey). For this purpose, a questionnaire, 'The Relationship Between Dental Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 27 publications
3
59
2
2
Order By: Relevance
“…[38][39][40] In a similar manner, differences in perceptions and attitudes towards various professional matters and issues of dental professionals' from different countries have also been documented. 27,[33][34][35][36]41 Despite the limited number of participants and within the limitations of the study design, the differences in the perceptions and attitudes of dentists towards CDGs observed in the present study are shaped by local circumstances. This may be of particular importance for attempts aiming at overcoming the barriers for effective implementation of CDGs into daily practice as each specific barrier may require a different approach again based on the local circumstances.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…[38][39][40] In a similar manner, differences in perceptions and attitudes towards various professional matters and issues of dental professionals' from different countries have also been documented. 27,[33][34][35][36]41 Despite the limited number of participants and within the limitations of the study design, the differences in the perceptions and attitudes of dentists towards CDGs observed in the present study are shaped by local circumstances. This may be of particular importance for attempts aiming at overcoming the barriers for effective implementation of CDGs into daily practice as each specific barrier may require a different approach again based on the local circumstances.…”
Section: Discussionmentioning
confidence: 71%
“…[27][28][29][30][31][32] For example, the impact of age, gender, years of practice and type of practice on the perceptions and attitudes of dental professionals regarding EBD was documented. 27 The present study is in line with these previous studies 27, 28 as a clear impact of age, gender, years of practice and 'type' of practice' on dentists perceptions and attitudes towards CDGs and their implementation into dental practice was concerned. Age and gender had impact even though type of practice seemed to have the most prominent impact.…”
Section: Protection Of Humans and Animalsmentioning
confidence: 99%
“…Cost efficiency should always be considered within best clinical practice, and it has been found that junior dentists are more likely to engage with such "evidence-based dentistry", when compared to older colleagues. 21 Therefore, encouraging change amongst younger practitioners (both EEA and UK trained) will be more likely to elicit a reform of duties within UK general dental practice, which could result in improved patient convenience and satisfaction, alongside reducing NHS expenditure on secondary care services.…”
Section: Discussionmentioning
confidence: 99%
“…EBD could help address this problem. However, finding reliable information is challenging and often the information is conflicting when consulting different sources (78)(79)(80). Indeed, in this study, our students reported difficulties in finding reliable information to answer the clinical questions (Fig.…”
Section: Student Opinions On Restorative Treatment Planningmentioning
confidence: 99%